Beyond Dualism: Hybrid Kiai Leadership and the Rise of One-Roof Islamic Education Governance - Taufikin Taufikin (JUMPA : Jurnal Manajemen Pendidikan, 2023)
The integration of Madrasah Ibtidaiyah (MI) and Islamic boarding schools under one roof presents a new configuration in Islamic education management that no longer separates formal and traditional systems. This study aims to reveal how the hybrid leadership of the kiai, serving as both the boarding school supervisor and the head of the madrasah, shapes a distinctive, layered governance pattern. Using a qualitative approach with an intrinsic case study design at MI Tahfidzul Qur’an and PPATQ Raudlatul Falah Pati, data were collected through observations of 530 students, in-depth interviews with the kiai, administrators, tahfiz teachers, murabbi, parents, and students, and the analysis of institutional documents. The findings indicate that the one roof system fosters an integration of authority that is not merely administrative but rooted in spiritual and cultural legitimacy. The management structure operates in a dual yet inseparable pattern, where formal and informal roles mutually reinforce one another. The curriculum is not merged but connected through the continuity of values between classroom learning and dormitory life. The educational environment fosters total control, enabling intensive and sustained character internalization. However, behind this integration, tensions emerge regarding professionalism and the distribution of authority. This study proposes the concept of Hybrid-Integrative Islamic School Governance (HIISG) as a synthesis between charismatic authority and managerial rationality in contemporary Islamic education. This concept expands the global discourse on value-based educational governance models that are both adaptive to tradition and responsive to the demands of modernity.